Fibrodysplasia ossificans progressiva: A rare disease with spinal deformity and severe hip dysfunction - Sun, Dong; Liu, Peng; Wang, Zhaolin; Mu, Jianhu; Cao, Jian (Frontiers in Pediatrics, 2022)
Introduction: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder characterized by congenital skeletal deformities and soft tissue masses that progress to heterotopic ossification. Congenital great toe deformity and progressive heterotopic ossifications with an anatomical and temporal pattern are the two classical clinical characteristics of FOP. We present a unique case of FOP characterized by mandibular angle fascial contracture and back and iliopsoas muscle ossification managed via surgery in a 13-year-old girl. Case presentation: A 13-year-old girl with a history of right cervical fascial release surgery and back heterotopic osteotomy presented to our clinic due to recurrence of heterotopic ossification, scoliosis, and rapidly advancing joint stiffness. Imaging study confirmed heterotopic ossification in the left back and left iliopsoas muscle and spinal scoliosis. Two years after the surgery, the patient presented with recurrence of back heterotopic ossification and rapidly advancing ossification of the left iliopsoas muscle. Six months after the tailored surgical resection, disability, pain, and clinical signs of recurrence were not observed, and the patient regained proper joint function. Conclusions: In patients with multiple-site heterotopic ossification caused by FOP, oral function and hip stiffness improve with detailed facial release surgery and rehabilitation treatment. However, dorsal fascia ossification and spinal scoliosis can recur shortly after resection.